2018
DOI: 10.1177/0897190018819413
|View full text |Cite
|
Sign up to set email alerts
|

Key Articles and Guidelines in the Management of Heart Failure: 2018 Update

Abstract: Heart failure is one of the leading causes of hospitalizations in the United States, with >1 million admissions yearly and a 25% risk of readmissions within 1 month. In order to assist clinicians, we provide an update of the heart failure bibliography that was published in Pharmacotherapy in 2008, which followed the original bibliography published in 2004. A significant number of clinical trials and observational studies have been conducted since the early 1980s to guide management of heart failure patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Heart failure is a formidable global public health challenge and is responsible for more than 1 million hospitalisations each year (Jackevicius et al, 2019). Heart failure describes a variety of cardiac structural or functional diseases that result in impaired ventricular filling or ejection capacity, insufficient blood perfusion in organs and tissues, and pulmonary or systemic circulation stasis (Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is a formidable global public health challenge and is responsible for more than 1 million hospitalisations each year (Jackevicius et al, 2019). Heart failure describes a variety of cardiac structural or functional diseases that result in impaired ventricular filling or ejection capacity, insufficient blood perfusion in organs and tissues, and pulmonary or systemic circulation stasis (Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2 The overall incidence of HF has been estimated to be 100-500 per 100 000 persons at risk in the general population, based on data from European countries and the USA. [3][4][5] Despite recent substantial improvements in medical care, 6 the outcome related with HF remains generally ominous. A recent systematic review and meta-analysis summarized survival data from 1.5 million patients with chronic HF across 60 studies; it was reported that the pooled survival rates at 1 month, 1, 2, 5, and 10 years were 65.7%, 86.5%, 72.6%, 56.7%, and 34.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%